Absorption fever characteristics due to percutaneous renal biopsy-related hematoma. Issue 37 (September 2016) - Hu, Tingyang; Liu, Qingquan; Xu, Qin; Liu, Hui; Feng, Yan; Qiu, Wenhui; Huang, Fei; Lv, Yongman
Abstract : Abstract: This study aims to describe the unique characteristics of absorption fever in patients with a hematoma after percutaneous renal biopsy (PRB) and distinguish it from secondary infection of hematoma. We retrospectively studied 2639 percutaneous renal biopsies of native kidneys. We compared the clinical characteristics between 2 groups: complication group (gross hematuria and/or perirenal hematoma) and no complication group. The axillary temperature of patients with a hematoma who presented with fever was measured at 06:00, 10:00, 14:00, and 18:00. The onset and duration of fever and the highest body temperature were recorded. Thereafter, we described the time distribution of absorption fever and obtained the curve of fever pattern. Of 2639 patients, PRB complications were observed in 154 (5.8%) patients. Perirenal hematoma was the most common complication, which occurred in 118 (4.5%) of biopsies, including 74 small hematoma cases (thickness ≤3 cm) and 44 large hematoma cases (thickness >3 cm). Major complications were observed in only 6 (0.2%) cases resulting from a large hematoma. Of 118 patients with a perirenal hematoma, absorption fever was observed in 48 cases. Furthermore, large hematomas had a 5.23-fold higher risk for absorption fever than the small ones. Blood pressure, renal insufficiency, and prothrombin time could be risk factors for complications. Fever is common in patients with hematoma because of renal biopsy and is usually noninfectious. Evaluation of patients with post-biopsy fever is necessary to identify any obvious infection sources. If no focus is identified, empiric antibiotic therapy should not be initiated nor should prophylactic antibiotics be extended for prolonged durations. Absorption fevers will resolve in time without specific therapeutic interventions.